AWARENESS, KNOWLEDGE AND ATTITUDE TOWARDS PHARMACOVIGILANCE AMONG MEDICAL GRADUATES IN A TERTIARY CARE TEACHING HOSPITAL IN SOUTH INDIA. - L, Arul Amutha Elizabeth; A, Arvinth; R, Susshimtha; P, Sowmiya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: As an ever growing scale people are using newer and more effective drugs for various medical conditions. Adverse drug reactions (ADRs) are preventable if the health-care professional pays close attention to the details of the adverse effects, following a drug administration. Awareness about ADRs can decrease the irrational use of drugs. Hence, there is an urgent need to create awareness among the prescribers about the ADR monitoring. Hence, this study is undertaken to assess the awareness, knowledge, and attitude toward Pharmacovigilance among the future health-care professionals. Methods: Questionnaire-based study was conducted in a tertiary health-care hospital after getting approval from the Institutional Ethical Committee. The questionnaire was developed to assess the knowledge, awareness, and practice of Pharmacovigilance activity. The questions were distributed to the final year students, interns, and postgraduate's students and allowed to write down the answers independently. Each correct answer was given a score of â€˜1,' whereas the incorrect/incomplete was given a score of 0.â€ Results and Conclusion: The study reported that awareness (UGs - 53.3%, interns - 54.9%, PGs - 30.75) was adequate among undergraduates and interns, in the knowledge part (UGs-65.5%, interns - 35.4%, PGs - 9.2%), undergraduates excel far than the interns and PGs. However, in the application of Pharmacovigilance (UG - 22.2%, interns - 59.8%, PGs - 63.1%) postgraduates and interns fair better than the undergraduates. Hence, there is need to increase the awareness and also increase the ADR reporting practice among medical graduates.